2017
DOI: 10.1039/c7nj00779e
|View full text |Cite
|
Sign up to set email alerts
|

First direct evidence of N-heterocyclic carbene in BMIm acetate ionic liquids. An electrochemical and chemical study on the role of temperature

Abstract: Cyclic voltammetry measurements provide the first direct evidence of N-heterocyclic carbene in neat 1-butyl-3-methylimidazolium acetate ionic liquid at temperatures over 120 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
3
30
1
Order By: Relevance
“…Nevertheless, the exogenous proton exchange equilibrium (1) is the only equilibrium of proton exchange operative involving Ac − at T < 60 °C (Scheme , eq. 1) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the exogenous proton exchange equilibrium (1) is the only equilibrium of proton exchange operative involving Ac − at T < 60 °C (Scheme , eq. 1) …”
Section: Resultsmentioning
confidence: 99%
“…1). [5] In fact, the effectiveness of an equilibrium of the endogenous proton exchange between BMIm + and Ac À , in pure BMImAc or in organic solvent at T < 60 8C, was definitively ruled out by us via electrochemical analysis that revealed that this equilibrium is operative at T > 60 8C. [13] As a consequence, in the Knovenagel mixture selected by us, the cation BMIm + behaves as a better counter ion of reactive anions Ac À and HCO 3 À as it shows a lower ion pairing ability than Na + and possibly enhances the reaction rate due to its hydrogen bond donor ability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 The existence of NHC derived from {[Bmim]AcO} was later determined at 120ºC by cyclic voltammetry (Scheme 1). 17 Thiazolium and imidazolium cations from ionic liquids as pre-catalysts in benzoin condensation-a mini review…”
Section: Formation Of N-heterocyclic Carbenes From Ionic Liquids Usedmentioning
confidence: 99%